Arterial and Venous Cerebral Blood Flow Velocities and Their Correlation in Healthy Volunteers and Traumatic Brain Injury Patients. Issue 1 (January 2022) - Cardim, Danilo; Czosnyka, Marek; Chandrapatham, Karthikka; Badenes, Rafael; Bertuccio, Alessandro; Corradi, Francesco; Donnelly, Joseph; Pelosi, Paolo; Hutchinson, Peter J.; Robba, Chiara
Abstract : Background: Few studies have explored the cerebral venous compartment or the correlation between venous and arterial cerebral blood flows. We aimed to correlate cerebral blood flow velocities in the arterial (middle cerebral artery) and venous (straight sinus) compartments in healthy volunteers and traumatic brain injury (TBI) patients. In addition, we determined the normative range of these parameters. Materials and Methods: A total of 122 healthy volunteers and 95 severe TBI patients of both sexes were included and stratified into 3 age groups as follows: group 1 (aged, 18 to 44 y); group 2 (aged, 45 to 64 y); group 3 (older than 65 y). Transcranial Doppler systolic cerebral blood flow velocity, diastolic cerebral blood flow velocity, and mean cerebral blood flow velocity (FVs, FVd, FVm, respectively) were measured in the middle cerebral artery and peak cerebral venous blood flow velocity (FVVs) was measured in the straight sinus. The arteriovenous correlation was assessed on the basis of a positive relationship between FVs and FVVs. Results: There was an arteriovenous correlation (FVs vs. FVVs) in healthy volunteers ( R =0.39, P <0.0001). We found no arteriovenous correlation in the TBI cohort overall, but FVs and FVVs were correlated in age group 1 ( R =0.28, P =0.05) and in males ( R =0.29, P =0.01). In healthy volunteers, FVs and FVm were significantly higher in males compared with females; and FVs, FVm, FVd, FVVs all increased across the age spectrum. There were no significant differences in any of these parameters in TBI patients. Conclusions: There are age and sex differences in arterial and venous cerebral blood flow velocities in healthy volunteers. Arteriovenous correlation is present in healthy volunteers but absent in TBI patients. Abstract : Supplemental Digital Content is available in the text.